Cross-Cultural Auditing: Challenges in Global Practice - Wulandari, Irma (Manunggal Halim Jaya, 2023)
This study explores the challenges faced by auditors in cross-cultural contexts, focusing on cultural biases, communication barriers, regulatory complexities, and trust dynamics. The research aims to investigate the impact of these challenges on audit practice and proposes strategies to mitigate them. A comprehensive literature review is conducted to identify key findings and insights. Methodologically, the study adopts a qualitative approach, drawing on existing literature and case studies to examine real-world examples of cross-cultural auditing challenges. The results highlight the pervasive influence of cultural biases and stereotypes on auditor judgment, the significance of clear and transparent communication in overcoming communication barriers, the complexity of navigating diverse regulatory environments, and the crucial role of trust in facilitating effective audit engagements. Furthermore, the study identifies strategies such as cultural awareness training, language proficiency development, regulatory compliance measures, and relationship-building activities to address these challenges. The findings underscore the importance of cultural intelligence development among audit professionals and emphasize the need for ongoing research and innovation in cross-cultural audit practices.